Profile of Extracurricular Physical Condition of Kickboxing and Muaythai Students of SMA Negeri 1 Ngawi - Fantas Setyadi (Edumaspul: Jurnal Pendidikan, 2023)
Physical condition is very necessary for professional and amateur class athletes, this is because physical condition will affect the performance of athletes. This study aims to determine the profile of the physical condition of students participating in extracurricular kickboxing and Muaythai at SMAN 1 Ngawi. The type of research used in this study is quantitative descriptive. This study used a data collection survey using measurement tests. The population of the study was 20 students from 10 extracurricular kickboxing participants and 10 Muaythai extracurricular participants, and total sampling was used in this study. Research using the instruments used, namely abdominal muscle strength using (Sit Up), leg muscle strength using (Standing Board Jump), arm muscle strength using (Push Up), speed using (Sprint 30m), flex using (Sit and Reach), power using (Vertical Jump), agility using (Illinois Run Test), and endurance using (MFT). The data analysis uses descriptive percentages. The results showed the profile of the physical condition of students participating in the extracurricular kickboxing SMAN 1 Ngawi in the "good" category with a total of 70% while the profile of the physical condition of students participating in the Muaythai SMAN 1 Ngawi extracurricular activity in the "good" category was 80%. The profile of the physical condition of students participating in extracurricular kickboxing SMAN 1 Ngawi and Muaythai SMAN 1 Ngawi is in the "good" category of 75%. From these results, it can be concluded that the overall physical condition of kickboxing and muaythai is included in the good category. So that the coach needs to improve the physical condition of the athlete, in order to achieve more optimal results.